Restorative Healing Environments: How can Mental, Physical and Spiritual Wellbeing be Improved through a Biophilic Design Approach? - Pretorius, Jana (School of Architecture, Planning and Geomatics, 2021)
People have become a lot more subject to a wide range of maladies from stress-related physical diseases, to psychological disorders, all the way to spiritual detachment. As Humans, we co-evolved alongside nature and the natural world. Human beings need contact with nature and the natural world. We need it to be healthy, happy and connected to live meaningful lives. Nature is not optional, it is absolutely necessary for a qualitative urban lifestyle. In order to live an effective pedestrianize living we will have to design compact and dense city to minimize the amount of traveling in between places. But compact and dense cities presents challenges to integrate nature and finding ways to make it possible for people in these environments to still be able to interact with nature and the natural environment on a daily basis. Connection with nature and the impact it has on our overall well-being is extremely important in a developing urban environment. E.O. Wilson, the father of the Biophilia Hypothesis, argues that our sense of belonging today comes from spending time in city parks, from the choices that we make for habitation, and from where people decide to spend their leisure time (Souter-Brown, 2015). Wilson states that we are hard-wired to be in nature, and it helps us to un-pack the fundamental idea of human nature and how people associate with themselves. Biophilic principles can be introduced to the public realm through bringing nature into pedestrianized spaces, creating a natural analogue, and creating vernacular spaces that draws reference to the contextual narratives of Cape Town. In this project we will look at different ways to re-introduce the natural world back into the artificial and urbanized city. The focus will be on the business district of Cape Town, where there is a recurring weekday interaction with the urban environment. Through creating a city park environment it will create a beneficial environment for daily commuters and pedestrians to benefit the mental, physical and spiritual well-being throughout our rapid urbanized city.